Immune Reconstitution Inflammatory Syndrome Secondary to Mycobacterium kansasii Infection in a Kidney Transplant Recipient. Issue 12 (15th September 2015) - Lemoine, M.; Laurent, C.; Hanoy, M.; Leporrier, J.; François, A.; Guerrot, D.; Godin, M.; Bertrand, D.
Abstract : Nontuberculous mycobacteria (NTM) infection is a challenging diagnosis for clinicians in solid organ transplantation. Immune reconstitution inflammatory syndrome (IRIS) is so far unreported in this context. We report here the case of a renal transplant recipient who developed Mycobacterium kansasii –associated lymphadenitis complicated by IRIS while undergoing reduction of his immunosuppressive therapy. For IRIS, the patient required low‐dose steroids and an increase in global immunosuppression, in association with NTM antibiotherapy. Abstract : The authors report an original case of immune reconstitution inflammatory syndrome secondary to Mycobacterium kansasii lymphadenitis in a kidney transplant patient, highlighting the importance of its recognition to manage an immunosuppression regimen.